2009
DOI: 10.2190/ec.40.1.e
|View full text |Cite
|
Sign up to set email alerts
|

Students' Problem Solving as Mediated by Their Cognitive Tool Use: A Study of Tool Use Patterns

Abstract: The purpose of this study was to use multiple data sources, both objective and subjective, to capture students' thinking processes as they were engaged in problem solving, examine the cognitive tool use patterns, and understand what tools were used and why they were used. The findings of this study confirmed previous research and provided clear empirical evidence supporting the theoretical notion that technology-based cognitive tools play an important role in assisting students' problem solving. Students' tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Although verifying such perceptions is not the focus of this study, the clear indication of students' enjoyment of the program and motivation to use it is an important step to help students learn. This finding is consistent with other studies that examined the effects of the PBL program on students' learning and motivation, showing significant gains in science knowledge (Liu, Hsieh, Cho, & Schallert, 2006;Liu et al, 2009;Liu, Horton, Olmanson, & Toprac, 2011).…”
Section: Classroom Goals As Written On the Boardsupporting
confidence: 91%
See 1 more Smart Citation
“…Although verifying such perceptions is not the focus of this study, the clear indication of students' enjoyment of the program and motivation to use it is an important step to help students learn. This finding is consistent with other studies that examined the effects of the PBL program on students' learning and motivation, showing significant gains in science knowledge (Liu, Hsieh, Cho, & Schallert, 2006;Liu et al, 2009;Liu, Horton, Olmanson, & Toprac, 2011).…”
Section: Classroom Goals As Written On the Boardsupporting
confidence: 91%
“…Although a set of cognitive tools (i.e. hard scaffolds) is provided in the program to assist problem solving (Liu et al, 2009), students must decide which cognitive tools to use, how to use them, and when to use them. The analysis also showed that because the software program provides many hard scaffolds (e.g., aiming at lowering cognitive load and supporting cognitive processes such as multimedia databases and a notebook tool), teachers can make best use of their time to address students' specific needs and promote higher-order thinking skills.…”
Section: Findings: Factors Affecting Teachers' Motivations To Adopt Amentioning
confidence: 99%
“…Regarding duration, students spent the longest in the Solar System Database (56.35 minutes), followed by the Alien Information Center (42.07 minutes) and Notebook (35.58 minutes); they spent only 0.90 minutes in the Mission Database. Previous studies (Liu et al, 2009(Liu et al, , 2016(Liu et al, , 2019 revealed that the Alien Information Center and the Solar System Database contain essential content information for understanding the aliens and our solar system. Therefore, the high frequency and long duration of use of these tools aligns with their importance in achieving the game's goals.…”
Section: Step 1: Descriptive Analysis Of Tool Use: Frequency and Dura...mentioning
confidence: 99%
“…The descriptive analysis of tool use showed that, in general, students spent more time and used essential tools more often in the game than non-essential tools. Previous studies (Liu et al, 2009(Liu et al, , 2016(Liu et al, , 2019 identified that four tools (e.g., Alien Information Center, Solar System Database, Probe Design Center, Mission Control Center) are essential in the game in that they contain information students must use to solve the problems and find the solutions. Our current findings regarding the overall patterns of essential tool usage in the game aligned with the previous research and emphasized the critical role of those essential tools in facilitating the learning process.…”
Section: The Connection Between Individual Tool Use and Student Perfo...mentioning
confidence: 99%
“…In the context of post-secondary education, the use of cognitive tools has been reported to improve students' satisfaction and learning of literacy (Lo, Affolter & Reeves, 2002), support medical diagnostic problem solving (Danielson et al, 2007), develop learners' ability in systems modelling and understanding (Hung, 2008), and enhance learners' problem solving and representation (Liu et al, 2009). In the area of veterinary medicine, Danielson et al (2007) used "diagnostic pathfinder" software as a cognitive tool and studied the impact of the tool on students' diagnostic problem-solving skills.…”
Section: Research On Cognitive Tools and Students' Learningmentioning
confidence: 99%